2012
DOI: 10.1177/0954406211433260
|View full text |Cite
|
Sign up to set email alerts
|

Surface and volumetric effects in a fluid subjected to high-frequency vibration

Abstract: In this article, the results of experimental study of surface and volumetric effects arising in a fluid under the action of high-frequency vibration are considered. Some elements in the theory of the surface effects are analyzed with regard to their origin and interrelations with other similar phenomena. The height of splashing fountains on the fluid surface is assessed based on the analogy with particle bounce over a vibrating plane. It is found that the influence of vibration on the average velocity of fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…1 With the wide application of the sheet metal hydroforming technology in aerospace, automotive and other fields, the related research is being carried out gradually. Yossif and Tirosh 2 and Blekhman et al 3 tried to substitute the rigid blank pressing for fluid pressure in the drawing. And he gave the reasonable fluid pressure scope by drawing test with aluminum, steel, copper in different thicknesses and friction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…1 With the wide application of the sheet metal hydroforming technology in aerospace, automotive and other fields, the related research is being carried out gradually. Yossif and Tirosh 2 and Blekhman et al 3 tried to substitute the rigid blank pressing for fluid pressure in the drawing. And he gave the reasonable fluid pressure scope by drawing test with aluminum, steel, copper in different thicknesses and friction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The further increase in frequencies resulted in emergence of standing waves ("cellular structures"). Cell dimensions tended to gradually decrease with the increase in ω so that at 146 rad/s frequency a gas-saturated turbulent layer of a gradually growing thickness was formed (for more details see [12]). The cells (standing waves) were found by theoretical analysis to correspond by their frequencies to a half of the liquid surface free oscillations in the gravity field λ, thus representing none other than Faraday ripple.…”
Section: Liquid In a Vibrating Vessel Cellular Structures Fountain mentioning
confidence: 99%
“…In our experiments [12] a cylindrical vessel of 60 mm diameter and 450 mm height was filled with water to 20, 50 and 100 mm levels. Vertical vibrations with 1 mm amplitude were imparted to the vessel, the frequencies ω increased from 75 to 240 rad/s.…”
Section: Liquid In a Vibrating Vessel Cellular Structures Fountain mentioning
confidence: 99%
“…Such studies have revealed that time-averaged forces, known as vibrational forces, occur in vibrating systems in addition to the forces that apply in analogous non-vibrating systems. It is these vibrational forces that lead to seemingly paradoxical phenomena, including the sinking of gas bubbles in vibrating liquids, and the levitation of fluid layers above air 2,3 . Vibrational forces have been used in practical applications, for example to enable the self-synchronization of the rotation of several bodies, and to separate and transport materials 7 .…”
mentioning
confidence: 99%